Comparative study of herbal bioenhancer containing nano formulation for oral delivery of paclitaxel: pharmacokinetic and cytotoxicity analysis (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The main objective of this study was to develop novel formulation containing herbal bioenhancer to increase the bioavailability of poorly water-soluble anticancer drug. Paclitaxel (PTX) loaded bioenhancer (Piperine and Quercetin) nanoparticle prepared by emulsification solvent evaporation method by using Eudragit RLPO as a polymer and to evaluate its in-vivo pharmacokinetics (PK) and cytotoxicity studies. The result is reduced oral bioavailability, which limits the use of paclitaxel, a crucial anticancer medication, when taken orally. Though multiple formulation approaches have been taken to fight this low absorption profile but consequence of different herbal bioenhancer, happening CYP3A and P-gp inhibitor on augmentation of bo plasma. Paclitaxel loaded nanoparticles with both bioenhancer used for this study and pharmacokinetic, cytotoxic study (MTT Assay) was used for comparative study. The prepared nanoparticles were evaluated for in vitro cell cytotoxicity study by MTT assay on lung cancer cell line and pharmacokinetic profile. The result revealed good in vitro properties with bioenhancer. The goal of the present work is to asses any modification in oral pharmacokinetics of paclitaxel. Therefore, it can be concluded that addition of bioenhancer with antitumor drug can enhance its prolifertive effect. However, further in vivo studies are recommended to establish the fact.